The Effectiveness of Story Method in Mutalaah Lessons for Character Education - Fuad, Ahmad; Yunus, Badruzzaman M.; Musthafa, Izzuddin; Nursobah, Asep (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2023)
Character education is essential, especially for the younger generation. Successful character education can be seen in students’ daily behavior, in how they apply vertical relation to God and horizontal regard to His creatures. To perform an effective character education, various methods and learning media can make students more excited at character values in the learning materials. The story method, mutalaah within the al-Qira’ah al-Rashidah Book 1 by Abdul Fatah Shabri Bik and Ali Amir Bik, includes some stories that contain noble morality. This study showed that character education through the story method has several stages, (1) the preparation of the syllabus and lesson plan, (2) the learning activity that covers opening, teaching-learning process, and closing. The process of planting moral values is carried out when a teacher explains the content and text of the lesson. Meanwhile, a formal evaluation is done in the semester test, besides daily assessment of student’s behavior in pesantren; (3) the story method through the learning mutalaah is considered effective in the development of morals because instinctively students like stories and are encouraged and motivated to practice the moral values in the mutalaah stories; (4) some factors supporting character education through the story method include the support of pesantren and principal, teacher’s linear educational background, and availability of decent infrastructure. On the contrary, the inhibiting factors include students’ diverse educational backgrounds, less motivation to study Arabic vocabulary, and lack of learning media that supports the delivery of learning materials.